YouTube as informal music learning resource for teenage users. Systematic review - Monreal-Guerrero, Inés María; Herrero Gozalo, Sara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article aims to carry out a systematic review of the scientific literature to shed light on the state of the art of YouTube as an informal music learning resource for teenage users. Nowadays, young people, digital natives and fluent users of social media and audio and video online platforms, constantly turn to YouTube as a ludic resource for their learning. However, having followed the parameters of a PRISMA systematic review, our study proves that there is a reduced amount of specific literature dealing with this particular topic.